Wilful Managerial Ignorance, Symbolic Work and Decoupling: A Socio-Phenomenological Study of 'Managing Creativity'. Issue 9 (September 2019) - Schaefer, Stephan M.
Ignorance has only received scant attention in organization and management studies. This paper focuses on ignorance in an organizational context by presenting and analysing the lived experience of three managers who attempted to manage creativity. The analysis of the empirical material with the help of a detailed agency framework illustrates how the managers' clearly articulated visions contradicted their practices and how they also stuck to their visions even when they were confronted with or had the possibility to collect information that would challenge those visions. I suggest, based on these observations, that the managers deliberately and actively avoided using or collecting relevant information that could potentially lead to transformative practices, which engendered what I call 'wilful managerial ignorance'. I further suggest that 'symbolic work', which refers to the active and continuous separation of verbal activity (symbol) and concrete practices (objective referent), is a determining factor in wilful managerial ignorance. Since wilful managerial ignorance and symbolic work prevent the productive and transformative integration of different institutional contexts it is possible to link it to the concept of 'decoupling'. As a result, I propose that wilful managerial ignorance and symbolic work are micro-determinants which facilitate the decoupling of organizationally relevant institutional contexts.